Cultural Norms of Clinical Simulation in Undergraduate Nursing Education - Susan G. McNiesh (SAGE Publishing, 2015)
Simulated practice of clinical skills has occurred in skills laboratories for generations, and there is strong evidence to support high-fidelity clinical simulation as an effective tool for learning performance-based skills. What are less known are the processes within clinical simulation environments that facilitate the learning of socially bound and integrated components of nursing practice. Our purpose in this study was to ethnographically describe the situated learning within a simulation laboratory for baccalaureate nursing students within the western United States. We gathered and analyzed data from observations of simulation sessions as well as interviews with students and faculty to produce a rich contextualization of the relationships, beliefs, practices, environmental factors, and theoretical underpinnings encoded in cultural norms of the students' situated practice within simulation. Our findings add to the evidence linking learning in simulation to the development of broad practice-based skills and clinical reasoning for undergraduate nursing students.